INTERNATIONAL EXPERIENCES IN COOPERATIVE AUDIT AND LESSONS FOR SERBIA - Zakić, Vladimir; Nikolić, Marija; Kovačević, Vlado (Economics of Agriculture, 2018)
Basic characteristics of cooperative audit, its role in preservation of cooperative nature and promotion of cooperatives are analyzed in the paper. The aim of this paper is to propose measures to improve cooperative audit in Serbia based on the review of good practice in European countries. The development stages of cooperative audit, from the creation of first cooperatives in Europe until today, have been examined using the historical method, with particular emphasis on the legislative framework that regulated this field. The comparative method was used to determine the differences between individual solutions, emphasizing their advantages and disadvantages, as well as the potential impact on the development of cooperatives. The research suggests that there are different solutions, from the absence of cooperative audit, to its inclusion in the cooperative life cycle, starting from its establishment. Although legislative framework in Serbia foresee cooperative audit, this process needs to be significantly improved.